Effect of narrow diameter polyaniline nanotubes and nanofibers in polyvinyl butyral coating on corrosion protective performance of mild steel - Mahmoudian, M.R.; Basirun, Wan Jefrey; Alias, Y. (Elsevier, 2012)
This study shows the effect of narrow diameter polyaniline (PAn) nanotubes and nanofibers in polyvinyl butyral coating on corrosion protective performance of mild steel. The PAn nanotubes and nanofibers were synthesised by chemical oxidative polymerisation in the presence of dodecylbenzene sulfonic acid (DBSA) as a bulky dopant acid. The molar ratios of monomer to DBSA used for the nanotube and the nanofiber synthesis are 1:1 and 4:1, respectively. Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) results confirm the narrow diameter range of 180-230 nm for the PAn nanotubes and nanofibers. Electrochemical impedance spectroscopy (EIS) confirms that the resistance of the coating containing PAn nanotubes is three times higher than the coating containing PAn nanofibers after 30 days of immersion. This effect can be explained because of the higher surface area of the nanotubes compared to nanofibers with the same mass. This difference increases the ability of PAn to interact with the ions liberated during the corrosion of the steel and increases the rate of cathodic reduction of oxygen on the surface of PAn. © 2012 Published by Elsevier B.V. All rights reserved.